PENGEMBANGAN KREATIVITAS MAHASISWA CALON GURU KIMIA DALAM PEMBELAJARAN DENGAN METODE INKUIRI LABORATORIUM MELALUI TEMA MINUMAN KEMASAN - Sari Sari; hayat solihin; muyati arifin (Department of Biology Education UIN Sunan Gunung Djati Bandung, 2015)
This study aims to find a laboratory inquiry learning model, obtain a description of students’ creativity development, and obtain a description of students’ responses toward using laboratory inquiry method with the theme of packaged beverage. The method in this study is quasi-experimental research design using Nonequivalent Control Group Design. The data is collected using creative thinking skill test, observation of attitude and action, as well as questionnaire. Quantitative data is analyzed using statistics. The results showed that the experimental class students experience the creative development from the aspects of creative thinking skills with the highest score is on the ability to think originally with N-gain of 42.13%in the moderate category. From the aspect of creative attitude, experimental class scores highest on the indicator of feeling challenged by a plurality by the N-gain of 59.25% in the moderate category. From the aspect of the creative act, the experimental class is highest on the performance aspects of lab implementation stage with average N-gain of 52.88% in the moderate category. Based on the results of the questionnaire, the students' responses to lab implementation, the ability to understand chemistry concepts through packaged beverage theme and their responses to learning method are positive.